MOSQUITO AVOIDANCE PRACTICES AND CORRELATES AMONG CARE-GIVERS OF UNDER-FIVE CHILDREN AT SOMOLU LOCAL GOVERNMENT AREA, LAGOS STATE. (2014)
Malaria control efforts currently lay emphasis on reducing transmission by limiting humanvector contact. Meanwhile, Mosquito-Avoidance Practices (MAPs) have been shown to be sub-optimal in urban areas especially among under-five Children (U-5C) resulting in high child morbidity and mortality. More studies have been carried out on MAPs in rural areas leaving urban areas understudied. This study was therefore designed to investigate MAPs among care-givers of U-5C living in Somolu, an urban Local Government Area (LGA) in Lagos State. A cross-sectional survey involving 394 female care-givers of U-5C selected using the Lot Quality Technique sampling method was conducted. The LGA was stratified into three based on the level of planning and drainage using Geographic Information System: well-planned well drained stratum (S1), well planned poorly drained stratum (S2) and unplanned and poorly drained stratum (S3). Data were collected using a semi-structured, intervieweradministered questionnaire, which elicited information on socio-economic characteristics, number of times U-5C had suspected malaria in the preceeding year, MAPs, bednet ownership and usage. Principal component analysis was used to calculate the household wealth index by listing household assets owned and categorized into five quintiles (poorest, second, third, fourth and richest quintiles). Data were analysed using descriptive statistics and Chi-square test at p=0.05. Age of respondents was 33.6±7.7 years. The proportion that earned ≥₦60,000 monthly in all strata were: S1-5.1%, S2-5.3% and S3-4.3% while those with tertiary education were: S1- 78.0%, S2-10.2% and S3-11.9%. Malaria transmission was attributed mostly to mosquito bites in all strata: S1-58.3%, S2-56.1% and S3-61.4%. The proportion of U-5C who had two episodes of suspected malaria in the preceeding year by strata were: S1-40.1%, S2-38.6% and S3-30.0%. The proportions who mentioned the mosquito net as a MAP by strata were: S1- 59.3%, S2-80.7% and S3-64.3%. The most reported MAP among U-5C was bednet: S1- 64.4%, S2-68.4% and S3-62.9%. Other MAPs reported included: spraying insecticide: S1- 20.5%, S2-26.3% and S3-17.1%, shutting door after sunset: S1-9.6%, S2-10.5% and S3- 11.4%, and clearing surroundings: S1-2.9%, S2-5.3% and S3-2.9%. Ownership of bednet was: S1-76.0%, S2-75.4% and S3-68.6% and out of these, S1-73.1%, S2-70.7% and S3- UNIVERSITY OF IBADAN LIBRARY vii 72.4%, reported that their child slept under the net the night before the survey. The MAPs across strata were not significantly different. Overall, 22.4% were in the richest quintile comprising: S1-79.5%, S2-9.1% and S3-11.4%. Majority of the respondents used just a single measure to prevent mosquito bite: S1-86.5%, S2-84.2% and S3-90.0%. Monthly earning ≥₦60,000, being in the richest wealth quintile, having tertiary education and knowing mosquito breeding site to be stagnant water were significantly associated with the use of multiple MAPs. The most common mosquito-avoidance practice among care-givers of under-five children was the use of bednet and this did not differ by level of planning and drainage of the study site. Therefore, strategies to improve and sustain the use of bednet and promote the use of other effective mosquito-avoidance practices should be encouraged. Keywords: Malaria control, Mosquito-avoidance practices, Care-givers, Under-five children Word count: 471